Adenovirus maturation establishes the transcription competent packaging of its genome - Baumgartl, Conradin; Holzinger, Simon; Schwartz, Uwe; Franken, Linda E.; Grünewald, Kay; Wodrich, Harald; Längst, Gernot (EMBO reports, 2025)
Adenoviruses are human pathogens that more recently have gathered interest as tools for human gene therapy and vaccination. The maturation of the viral genome with associated proteins (core) remains largely unexplored. Here, we show that adenovirus core maturation is guided by features embedded in the viral DNA sequence, which primes the genome for transcription. Using DMS-seq to compare the accessibility of the nucleoprotein core structure before and after maturation (using the maturation deficient ts1 mutant), we identified five genomic regions that become specifically decompacted during maturation. These regions are characterized by low GC-content and are evolutionarily conserved across different adenovirus species, independent of protein-coding constraints. Adenoviral DNA packaging is guided by a distinct 6.1-bp dinucleotide periodicity pattern that helps position viral chromatin proteins. Core maturation serves a dual purpose: (i) it contributes to capsid uncoating by increasing internal pressure while (ii) simultaneously preparing the viral chromatin structure for rapid transcription upon nuclear entry. These findings reveal how sequence-encoded structural information guides adenoviral genome organization and suggest new approaches for optimizing therapeutical adenoviral vectors.